Paramedic educational program attrition accounts for significant loss of potential EMS workforce - Matthew Ball; Jonathan R. Powell; Christopher B. Gage; Katelynn A. Kapalo; Jordan D. Kurth; Lisa Collard; Michael G. Miller; Ashish R. Panchal (Journal of the American College of Emergency Physicians Open)
Abstract Objective Recent concerns for the strength and stability of the emergency medical services (EMS) workforce have fueled interest in enhancing the entry of EMS clinicians into the workforce. However, the educational challenges associated with workforce entry remain unclear. Our objective was to evaluate the educational pathway of entry into the EMS workforce and to identify factors that lead to the loss of potential EMS clinicians. Methods This is a cross‐sectional evaluation of all US paramedic educational programs, with enrolled students, in the 2019 Committee on Accreditation of Educational Programs for the EMS Professions annual report survey. This data set includes detailed program characteristics and metrics including program attrition rate (leaving before completion), and certifying exam pass rates. Descriptive statistics were calculated, and multivariable logistic regression analysis was conducted to evaluate the association between high program attrition rates (>30%) and program specific characteristics. Results In 2019, 640 accredited programs met inclusion with 17,457 students enrolled in paramedic educational programs. Of these, 13,884 students successfully graduated (lost to attrition, 3,573/17,457 [21%]) and 12,002 passed the certifying exam on the third attempt (lost to unable to certify, 1,882/17,457 [11%]). High program attrition rates were associated with longer programs (>12 months), small class sizes (<12 students), and regional locations. Conclusions Nearly 1 in 3 paramedic students were lost from the potentially available workforce either owing to attrition during the educational program or failure to certify after course completion. Attrition represented the largest loss, providing an avenue for future targeted research and interventions to improve EMS workforce stability.